Między fantastyką i aluzją. SOCIAL FICTION jako kryptopolityczny nurt polskiej literatury lat siedemdziesiątych i osiemdziesiątych XX wieku - Mazurkiewicz, Adam (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
This article focuses on Polish science fiction of the 70's and 80's in the 20th century. It seeks to present the way the writers used artistic strategies for creating the parable of the Polish political reality. The analyses of the vision of the presented world refer to the works by Janusz A. Zajdel, Wiktor Żwikiewicz, Marek Oramus and Edmund Wnuk-Lipiński.